EFFECTS OF STRATEGIC PLANNING ON THE FINANCIAL PERFORMANCE OF SMALL INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) FIRMS IN NAIROBI CITY COUNTY - Midiwo, Peninah Awuor; Ombui, Dr. Kepha (European Journal of Business and Strategic Management, 2018)
Purpose: The main objective of the study was to determine the effect of strategic planning on the financial performance of small ICT companies in Nairobi County. Methodology: The descriptive research design was adopted in the study. A total of 584 small ICT companies based in Nairobi County formed the target population. The researcher grouped the population into strata according to their years in operation. Due to time and resource constraints, it was not possible to study the entire population. A sample of 232 small ICT companies was therefore selected from the target population to participate in the study. Respondents consisted of one member from the top management of each company in the sample. The main data collection instrument was questionnaires. The questionnaires were distributed to the respondents. Respondents were expected to complete the questionnaires within a period of two weeks, after which the researcher personally collected them. Data collected was analyzed using SPSS. To determine the effect of the four independent variables on the dependent variable, multiple regression was applied. Tables and charts were used to present the results of the study. Results: From the results, strategic planning in the confines of environmental scanning, formality, time horizon and evaluation was found to have a significant effect on financial performance, collectively accounting for 60% for the changes in the financial performance of small ICT companies. An ANOVA test revealed that environmental scanning, formality and evaluation have a significant effect on the financial performance of small ICT companies. Time horizon was however found to have no significant effect on financial performance of small ICT companies. The study therefore concluded that strategic planning has a positive effect on the financial performance of small ICT companies in Nairobi County. Unique Contribution to Theory, Practice and Policy: The study recommends that there is need for the government, policy makers and regulators to provide regular information and insight into the ICT sector. This information can be beneficial in understanding the contribution of the sector, services on demand, service providers, technologies, the state of competition, compliance requirements and regulations..